2018
DOI: 10.29252/ijrm.16.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Female genital tuberculosis cases with distinct clinical symptoms: Four case reports

Abstract: Background:Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Genital TB (GTB) is a form of extrapulmonary TB that occurs more frequently in women, in whom it classically presents in association with menstrual irregularity, pregnancy loss and short and long-term sequelae especially infertility in infected women. Patients with GTB are usually young women diagnosed during workup for infertility. GTB is rare in postmenopausal women and responsible for only approximately 1% of postmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…This scenario is not uncommon, as numerous studies have reported similar phenomenon. 7,8 Our patient experienced an increasing abdominal distention and pain which are common early presentation of FG-TB. In addition, the patient also presented with typical gastrointestinal symptoms such as early satiety, nausea, and vomiting, similar to what has been reported in other cases.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This scenario is not uncommon, as numerous studies have reported similar phenomenon. 7,8 Our patient experienced an increasing abdominal distention and pain which are common early presentation of FG-TB. In addition, the patient also presented with typical gastrointestinal symptoms such as early satiety, nausea, and vomiting, similar to what has been reported in other cases.…”
Section: Discussionmentioning
confidence: 85%
“…For example, a study looking at endometrial TB found inferiority in histopathological diagnosis compared with PCR, where paucity in diagnosing TB is high with use of Ziehl-Neelsen stain and even culture was reported to be challenging in diagnosing FG-TB. [6][7][8][9] The mainstay for treatment of FG-TB is daily use of rifampicin (R), isoniazid (H), pyrazinamide (Z), and ethambutol for 2 months, followed by daily therapy with two out of the four drugs: rifampicin (R) and isoniazid (H). 1,7 Our patient had neither personal nor family history of TB, and she had no any conventional TB-related symptoms such as weight loss, night sweats, or fever.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the female genital site remains underestimated and rarely cited in the literature, which explains the delay in diagnosis. The exact prevalence of female genital tuberculosis is difficult to specify because of many cases that are often asymptomatic [ 1 , 5 ]. The young age observed in the patients of our series is also reported in other African and Asian series, and could be explained by early marriages and pregnancies in this population [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis is of significant public health importance globally, with the largest number of diseases documented in sub-Saharan Africa [ 1 ]. The World Health Organization (WHO) estimated about 10.4 million tuberculosis cases with about 1.8 million deaths from TB in 2015 worldwide [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…12 Women with PTB are usually younger than women with ovarian malignancies, ranging from 20-40 years, with a less progressive clinical picture than ovarian malignancies. 13 Most patients present with unexplained manifestation of abdominal pain (50-100% of cases), weight loss (50-61%), fever (13-59%), distension due to ascites (40-73%), abdominal mass, abdominal tenderness, and night sweats (65). 7, 14 Due to slow progressivity of symptoms, patients tend to show symptoms for months before seeking medical care.…”
Section: Discussionmentioning
confidence: 99%